Ethnic diversity on boards and market performance: An empirical investigation in Malaysia - Hassan, R. (American Scientific Publishers, 2015)
This study seeks to examine the relationship between ethnic diversity among board members and market value of listed firms in Malaysia. Ethnic diversity is defined as the number of non-bumiputra (Chinese, Indian) on the board of directors. The concept of value-in-diversity argues that a diverse workforce is beneficial for business organization. Diverse members of boards enhance the overall performance of the organization. Literature shows that there is ambiguity among previous researches. The results seem to be inconsistent. There is a need to investigate this issue in a more holistic way. This research is unique and first of its kind that consider the relationship between ethnic diversity on boards with market value. The results indicate that ethnic diversity does have an impact on market value, but they are inversely correlated. The results also indicate that the proportion of non-bumiputra on boards tends to increase with the increasing members on board. However, ethnic diversity is negatively associated with market performance. The outcomes of the research help to shareholders, and other stakeholders, including the potential investors and policy makers to understand the significance of ethnic diversity at top level management. Â© 2015 American Scientific Publishers. All rights reserved.